HLA class II peptide tetramers vs allergen‐induced proliferation for identification of allergen‐specific CD4 T cells. Issue 1 (28th November 2014) - Van Hemelen, D.; Mahler, V.; Fischer, G.; Fae, I.; Reichl‐Leb, V.; Pickl, W.; Jutel, M.; Smolinska, S.; Ebner, C.; Bohle, B.; Jahn‐Schmid, B.
Abstract Background Fluorescence‐labeled MHC class II/peptide tetramer complexes are considered as optimal tools to characterize allergen‐specific CD4+ T cells, but this technique is restricted to frequently expressed HLA class II molecules and knowledge of immunodominant epitopes. In contrast, allergen‐stimulated proliferation assessed by CFSE dilution is less sophisticated and widely applicable. The major mugwort allergen, Art v 1, contains only one single, immunodominant, HLA‐DR1‐restricted epitope (Art v 125‐36). Thus, essentially all Art v 1‐reactive cells should be identified by a HLA‐DRB1*01:01/Art v 119‐36 tetramer. Methods We compared specificity and sensitivity of tetramer+ and allergen‐induced proliferating (CFSElo) CD4+ T cells by flow cytometry. Results The frequency of tetramer+ CD4+ T cells determined ex vivo in PBMC of mugwort‐allergic individuals ranged from 0 to 0.029%. After 2–3 weeks of in vitro expansion, sufficient tetramer+ T cells for phenotyping were detected in 83% of Art v 125‐36‐reactive T‐cell lines (TCL) from mugwort‐allergic individuals, but not in TCL from healthy individuals. The tetramers defined bona fide Th2 cells. Notably, Art v 125‐36‐reactive TCL depleted of tetramer+ T cells still reacted to the peptide, and only 44% of Art v 125‐36‐specific T‐cell clones were detected by the tetramer. CFSElo CD4+ T cells contained only 0.3–10.7% of tetramer+ T cells and very low proportions of Th2 cells. Conclusion Allergen‐specific T cells can be identified by HLA class II tetramers with high specificity, but unexpected low sensitivity. In contrast, allergen‐stimulated CFSElo CD4+ T cells contain extremely high fractions of bystander cells. Therefore, for T‐cell monitoring, either method should be interpreted with caution.